Interactions Among Pratylenchus penetrans, P. scribneri, and Verticillium dahliae in the Potato Early Dying Disease Complex - Wheeler, T. A. (Society of Nematologists, 1994)
Microplots were infested with combinations of the fungus Verticillium dahliae and Pratylenchus penetrans and P. scribneri to test for individual and combined effects of these organisms on potato yield and nematode reproduction. Verticillium dahliae alone caused yield losses in all 3 years of the experiment, and the interaction between P. penetrans and V. dahliae was significant (P ≤ 0.05) in 2 years. Pratylenchus penetrans alone caused yield losses in 2 years and P. scribneri alone caused yield losses in 1 year. No two-way or three-way interaction was found involving P. scribneri. In 1987, reproduction for low densities of P. penetrans was 5 times higher when P. scribneri was also present than when it was absent, and 3.5 times higher in 1988. In nematode species mixtures, reproduction of P. scribneri was decreased by V. dahliae in 1987-88. The final population density of P. scribneri was negatively affected by V. dahliae and positively related to the initial proportion of P. scribneri to P. penetrans. In species mixtures with proportions of P. penetrans ranging from 0.1 to 0.5, reproduction of P. penetrans was negatively affected by V. dahliae and decreased linearly in relation to the increase in the initial proportion of P. penetrans in both years. The final population density of P. penetrans was affected only by V. dahliae.